Hippocampal Testosterone Relates to Reference Memory Performance and Synaptic Plasticity in Male Rats - Schulz, Kristina; Korz, Volker (Frontiers in Behavioral Neuroscience, 2010)
Steroids are important neuromodulators influencing cognitive performance and synaptic plasticity. While the majority of literature concerns adrenal- and gonadectomized animals, very little is known about the “natural” endogenous release of hormones during learning. Therefore, we measured blood and brain (hippocampus, prefrontal cortex) testosterone, estradiol, and corticosterone concentrations of intact male rats undergoing a spatial learning paradigm which is known to reinforce hippocampal plasticity. We found significant modulations of all investigated hormones over the training course. Corticosterone and testosterone were correlated manifold with behaviour, while estradiol expressed fewer correlations. In the recall session, testosterone was tightly coupled to reference memory performance, which is crucial for reinforcement of synaptic plasticity in the dentate gyrus. Intriguingly, prefrontal cortex and hippocampal levels related differentially to reference memory performance. Correlations of testosterone and corticosterone switched from unspecific activity to specific cognitive functions over training. Correspondingly, exogenous application of testosterone revealed different effects on synaptic and neuronal plasticity in trained versus untrained animals. While hippocampal long-term potentiation (LTP) of the field excitatory postsynaptic potential (fEPSP) was prolonged in untrained rats, both the fEPSP- and the population spike amplitude-LTP was impaired in trained rats. Behavioural performance was unaffected, but correlations of hippocampal field potentials with behaviour were decoupled in treated rats. The data provide important evidence that besides adrenal, also gonadal steroids play a mechanistic role in linking synaptic plasticity to cognitive performance.